Identifying Influential Factors in a Comprehensive Strategic Marketing Model Based on Economic Diplomacy with a Grounded Theory Approach - Nikbakht, Ahmad; Pirzad, Ali; Mousavi, Seyed Najmeddin (International Journal of Innovation Management and Organizational Behavior (IJIMOB), 2024)
Objective: The aim of this research is to identify influential factors in a comprehensive strategic marketing model based on economic diplomacy using a grounded theory approach. Methodology: In this study, a comprehensive strategic marketing model was developed using qualitative methods and analyzing data collected from in-depth interviews with experts and specialists in the fields of marketing and economic diplomacy.Findings: The research findings indicate that key factors including government policies, international relations, commercial infrastructure, technical and scientific capabilities, organizational culture, and knowledge management play crucial roles in the success of marketing strategies based on economic diplomacy. Additionally, the ability to create and maintain effective communication networks with other countries, the use of modern technologies, and innovation in products and services were identified as facilitating and strengthening factors for international marketing.Conclusion: Based on the findings of this research, a comprehensive strategic marketing model based on economic diplomacy is presented, which can be used as a framework for developing and implementing marketing strategies at the international level. This model, with an emphasis on the role of economic diplomacy and attention to the identified key factors, can help improve marketing performance and enhance the competitiveness of countries in the global market. This research, by presenting a theoretical model based on grounded theory, adds to the existing knowledge in the field of international marketing and economic diplomacy and proposes practical solutions for improving marketing strategies in this area.